The relationship between the servant leadership and employee performance among lecturer in UiTM Jengka, Pahang / Fatin Nabilah Azmi - Azmi, Fatin Nabilah (Faculty of Business and Management, 2019)
The final report project was carried out in order to fulfil the requirement of the Academic Project (ASM601). The study will be conducted at the government organizations at Pahang. There are two main objectives are to identify employees' performance level in the organization and to identify the relationship between servant leadership and employee performance in the organization. By referring to Krejcie and Morgan table (1970), the scopes are focused on the certain number of population. The sample sizes are taken referred to the sample size for a given population. The convenience sampling technique is easy but should have been distributed randomly. The data will be analysed and interpreted using SPSS software. It is hope that from the overall findings, we could discover that employees at UiTM Cawangan Pahang, Kampus Jengka to have a servant leaders at office. The employees are able to know more about the elements of servant leadership which are agape love, services, trust and humility. It is hope that the more significant it is toward handling the issues among them.